Price cost margins and exporting behaviour: Evidence from firm level data - Holger Görg; Frederic Warzynski (Katholieke Universiteit Leuven, LICOS Centre for Transition Economics, 2003)
This paper examines whether exporting activity matters for ffirm's price cost margins. The recent literature on exporting and productivity shows that exporters on average are more efficient than nonexporters. If that is the case we may also expect them to have different mark-ups. We investigate this issue using company level data for UK manufacturing industries. The measurement of mark-ups follows the recent approach presented by Roeger (1995). Our results show that, on average, exporters have higher mark-ups than non-exporters. We also distinguish sectors into homogeneous and differentiated goods producing. This distinction shows that we only find higher mark-ups for exporters in differentiated goods sectors, not in homogeneous sectors
Keywords: 330; Außenhandelspreis; Mark-up Pricing; Betriebliche Preispolitik; Internationaler Wettbewerb; Produktivität; Großbritannien